Anxiety and Related Disorders and Concealment in Sexual Minority Young Adults. Issue 1 (January 2016) - Cohen, Jeffrey M.; Blasey, Christine; Barr Taylor, C.; Weiss, Brandon J.; Newman, Michelle G.
Abstract: Sexual minorities face greater exposure to discrimination and rejection than heterosexuals. Given these threats, sexual minorities may engage in sexual orientation concealment in order to avoid danger. This social stigma and minority stress places sexual minorities at risk for anxiety and related disorders. Given that three fourths of anxiety disorder onset occurs before the age of 24, the current study investigated the symptoms of generalized anxiety disorder, social phobia, panic disorder, posttraumatic stress disorder, and depression in sexual minority young adults relative to their heterosexual peers. Secondarily, the study investigated sexual orientation concealment as a predictor of anxiety and related disorders. A sample of 157 sexual minority and 157 heterosexual young adults matched on age and gender completed self-report measures of the aforementioned disorders, and indicated their level of sexual orientation concealment. Results revealed that sexual minority young adults reported greater symptoms relative to heterosexuals across all outcome measures. There were no interactions between sexual minority status and gender, however, women had higher symptoms across all disorders. Sexual minority young women appeared to be at the most risk for clinical levels of anxiety and related disorders. In addition, concealment of sexual orientation significantly predicted symptoms of social phobia. Implications are offered for the cognitive and behavioral treatment of anxiety and related disorders in this population. Highlights: We investigate anxiety and related disorders in sexual minority young adults. We investigate sexual orientation concealment as a predictor of disorders. Sexual minorities displayed higher symptoms of anxiety and related disorders. Sexual minority women appear to be at the most risk for anxiety and related disorders. Sexual orientation concealment was associated social phobia in sexual minorities.